NEW DIRECTIONS FOR IMPROVEMENT OF BREAST CANCER SCREENING - N. V. Kochergina; A. B. Bludov; Ya. A. Shchipakhina; O. V. Ivankina; M. S. Karpova; I. L. Kiselev; B. I. Dolgushin (Вестник рентгенологии и радиологии, 2017)
Objective: to improve breast cancer diagnosis using an independent mammographic teleassessment by two radiologists. Material and methods. The results of a dual independent assessment of 3440 X-ray mammographic examinations were analyzed. The first assessment was made by a radiologist from a therapeutic-and-prophylactic establishment who had less than one year of practical experience in a mammography screening room. The second assessment was carried out by a radiologist with more than 5 years of experience from a specialized cancer institution. Results. According to the developed specialized interpretation software, recommendations and statistics for mammographic breast cancer screening, the investigators identified a group of 31 women who were recommended to be additionally examined at an oncology dispensary to verify the diagnosis of breast cancer. Eight of 17 (47%) women with morphologically confirmed cancers after dual assessments of X-ray mammographs were called again and referred to the oncology dispensary. Conclusion. Dual independent assessment of X-ray mammographs improved the diagnosis of BC with a maximum size of 1.5 cm or less, as well as that of malignant tumors manifesting as microcalcifications or imitating a benign process.